2018
DOI: 10.1200/cci.18.00054
|View full text |Cite
|
Sign up to set email alerts
|

A Behavior-Modification, Clinical-Grade Mobile Application to Improve Breast Cancer Survivors' Accountability and Health Outcomes

Abstract: Purpose Only 34% of breast cancer survivors engage in the recommended level of physical activity because of a lack of accountability and motivation. Methodist Hospital Cancer Health Application (MOCHA) is a smartphone tool created specifically for self-reinforcement for patients with cancer through the daily accounting of activity and nutrition and direct interaction with clinical dietitians. We hypothesize that use of MOCHA will improve the accountability of breast cancer survivors and help them reach their p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
33
0
8

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(41 citation statements)
references
References 25 publications
0
33
0
8
Order By: Relevance
“…6 The utilization of Mobile applications is associated with increased cancer knowledge 8 and provides real-time feedback. 9 Similarly, telemedicine via videoconference is equal in patient satisfaction and perceived quality of care. 4 Surprisingly in our study (mobile application and telemedicine) were not the preferred method and this is likely due to similar technology-specific reasons described by Scott Kruse et al, 19 and we need better ways to assess the quality and effectiveness of mobile health applications.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…6 The utilization of Mobile applications is associated with increased cancer knowledge 8 and provides real-time feedback. 9 Similarly, telemedicine via videoconference is equal in patient satisfaction and perceived quality of care. 4 Surprisingly in our study (mobile application and telemedicine) were not the preferred method and this is likely due to similar technology-specific reasons described by Scott Kruse et al, 19 and we need better ways to assess the quality and effectiveness of mobile health applications.…”
Section: Discussionmentioning
confidence: 99%
“…8 Mobile health applications improved goal adherence for breast cancer survivors by providing real-time feedback and accountability with the health care team. 9 Digital transformation is the integration of digital technology with patients, healthcare providers and regulators. 10 Healthcare transformation will add an opportunity to translate new data into actionable information, allowing earlier diagnosis and precise treatment options.…”
Section: Introductionmentioning
confidence: 99%
“…The results showed a decreased level of post-traumatic stress symptoms. In another study led by Stubbins et al (2018), a mobile app-based CBT program that aimed to increase the physical activity of breast cancer survivors was developed and examined for its effectiveness in 33 survivors over 4 weeks; the results showed that the program was effective for weight loss. The study by Greer et al (2017) is the only one in which a mobile app-based CBT program was developed with the goal of reducing depression and anxiety symptoms in cancer patients.…”
Section: Introductionmentioning
confidence: 99%
“…We identified two common themes for the use of mobile health apps in tertiary breast cancer prevention: clinical care coordination and health related quality of life during and after a breast cancer diagnosis. Cancer care coordination studies focused on the support and communication between the breast cancer patient and the physician (32, 41, 47, 48, 66, 68), as well as specific aspects of cancer care coordination, such as symptomology (12, 14, 23, 27, 52), medication adherence (23, 34, 38, 45, 66), and ambulatory surgery (7, 8). Research using apps designed to improve health related quality of life focused on general lifestyle management (30, 42, 56, 60, 64, 69), weight management (61, 66, 67), depression and breast cancer related distress (12, 17, 21, 23, 37, 63), social support (12, 40, 50, 51), sleep (20), and physical activity during and after a breast cancer diagnosis (9, 11, 22, 24, 25, 28, 29, 33, 35, 36, 46, 55, 59, 65).…”
Section: Resultsmentioning
confidence: 99%